KAJIAN ASINONIMITAS AL-KITAB WAL ALQUR’AN: QIRA’AH MUASHIRAH - Mia Fitriah Elkarimah (Pusat Pengembangan Bahasa IAIN Tulungagung, 2017)
This research aimed to describe the concept of Muhammad Syahrur in reviewing texts of the Qur’an by not using synonyms in the Qur’an, it’s called a-synonymy. synonyms in the Qur’an is often discussed, and the scholars of Arabic linguists was divided into two opinions whether there is the existence of synonyms in the Qur’an or not, most of them agree but others disagree for several reasons. one of them is Muhammad Syahrur. This reseach used analytical descriptions and linguistic approach. The frst data source used his book “ al-Kitabwal al-Qur’an; Qira’ahMuashirah”, From analytical descriptions the writer can elaborate of Syahrur’s linguistic approachby analyzing the meanings contained in that verses by using analysis of syntagmatic and paradigmatic analysis and integrate the concepts that have been obtained to acquire a special meaning in the Qur’an, from that we can take Syahrur’s textual context of the verses being studied.